Loneliness in Working and Non-Working Young Adult Women - Niazi, Rehana Batool; Mushtaq, Rehana; Bibi, Jamila (Annals of Human and Social Sciences, 2025)
This study compares loneliness levels between employed and non-employed young adult women in Islamabad and Rawalpindi, Pakistan. Employment is believed to play a protective role against loneliness by offering social interaction, identity, and structure. This study examines whether vocational engagement reduces perceived loneliness among women. A purposive sample of 60 women aged 25–30 years (30 employed, 30 non-employed) was assessed using the UCLA Loneliness Scale (Version 3). Data were analyzed using an independent samples t-test in SPSS. Findings revealed that non-employed women reported significantly higher loneliness scores than employed women, suggesting that employment contributes to emotional and social well-being. To reduce loneliness among non-working women, it is recommended to implement community-based programs, support groups, and skill-building workshops that foster social engagement and self-worth. Policymakers and mental health professionals should promote inclusive initiatives that enhance psychological well-being through structured roles and social support systems.